Dietary Management of Blood Glucose in Medical Critically Ill Overweight and Obese Patients: An Open‐Label Randomized Trial. Issue 4 (27th September 2018) - Rice, Todd W.; Files, D. Clark; Morris, Peter E.; Bernard, Andrew C.; Ziegler, Thomas R.; Drover, John W.; Kress, John P.; Ham, Kealy R.; Grathwohl, Dominik J.; Huhmann, Maureen B.; Gautier, Juan B. Ochoa
Abstract: Background : Enteral nutrition (EN) increases hyperglycemia due to high carbohydrate concentrations while providing insufficient protein. The study tested whether an EN formula with very high‐protein‐ and low‐carbohydrate‐facilitated glucose control delivered higher protein concentrations within a hypocaloric protocol. Methods : This was a multicenter, randomized, open‐label clinical trial with parallel design in overweight/obese mechanically ventilated critically ill patients prescribed 1.5 g protein/kg ideal body weight/day. Patients received either an experimental very high‐protein (37%) and low‐carbohydrate (29%) or control high‐protein (25%) and conventional‐carbohydrate (45%) EN formula. Results : A prespecified interim analysis was performed after enrollment of 105 patients (52 experimental, 53 control). Protein and energy delivery for controls and experimental groups on days 1–5 were 1.2 ± 0.4 and 1.1 ± 0.3 g/kg ideal body weight/day ( P = .83), and 18.2 ± 6.0 and 12.5 ± 3.7 kcals/kg ideal body weight/day ( P < .0001), respectively. The combined rate of glucose events outside the range of >110 and ≤150 mg/dL were not different ( P = .54, primary endpoint); thereby the trial was terminated. The mean blood glucose for the control and the experimental groups were 138 (−SD 108, +SD 177) and 126 (−SD 99, +SD 160) mg/dL ( P = .004), respectively. Mean rate of glucose events >150 mg/dL decreased (Δ = −13%, P = .015), whereas that of 80–110 mg/dL increased (Δ = 14%, P = .0007). Insulin administration decreased 10.9% (95% CI, −22% to 0.1%; P = .048) in the experimental group relative to the controls. Glycemic events ≤80 mg/dL and rescue dextrose use were not different ( P = .23 and P = .53). Conclusions : A very high‐protein and low‐carbohydrate EN formula in a hypocaloric protocol reduces hyperglycemic events and insulin requirements while increasing glycemic events between 80–110 mg/dL.